Evaluation of the reliability of soccer-specific field tests - Mirkov, D.; Nedeljkovic, A.; Kukolj, M.; Ugarkovic, D.; Jaric, S. (The Journal of Strength and Conditioning Research, 2008)
The soccer-specific field tests are popular among coaches due to their simplicity, validity, and minimal use of equipment. Nevertheless, there is a general lack of data about their reliability, particularly regarding the tests of anaerobic performance. Twenty professional male soccer players performed 3 consecutive trials of the tests of throwing-in and standing-kick performance (the distance measured) as well as on timed 10-m sprint, flying 20-m sprint, running 10 x 5 m, zigzag running with and without the ball, and the skill index (i.e., the ratio of the zigzag running without and with the ball). With the exception of the throwing-in and standing kick, the evaluated tests revealed high intraclass correlation coefficients (i.e., >0.80), small within-individual variations (coefficient of variation, <4%), and sample sizes for detecting a 2% change in the tested performance that are either close to or below the standard size of a professional soccer squad. In addition to simplicity and face validity, most of the evaluated tests revealed high reliability. Therefore, the evaluated tests are recommended for sport-specific profiling and early selection of young athletes as well as for routine testing procedures that could detect effects of various intervention procedures. Regarding the throwing-in and standing-kick tests, direct measurement of the ball velocity (e.g., with a standard radar gun) is recommended.